2018
DOI: 10.1016/j.preghy.2017.11.009
|View full text |Cite|
|
Sign up to set email alerts
|

The feasibility and acceptability of self-testing for proteinuria during pregnancy: A mixed methods approach

Abstract: A B S T R A C TObjective: To investigate feasibility and acceptability of self-testing for proteinuria during pregnancy. Study design: Mixed methods approach which included: an accuracy study where pregnant women (n = 100) and healthcare professionals (n = 96) tested seven synthetic protein samples and completed a questionnaire, a feasibility study where pregnant women who were self-monitoring their blood pressure were asked to self-test for proteinuria (n = 30), and an online questionnaire about women's exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…Self-testing was not common though most respondents thought that women would find self-testing acceptable, which fits with other research in the area. [23] While self-testing was valued, nearly all of those supporting home-testing would repeat the measurement in clinic, typically in order to perform an up-to-date reading. Practice and views became more positive with the implementation of remote monitoring due to the pandemic, though with much lower levels of acceptability than BP self-monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Self-testing was not common though most respondents thought that women would find self-testing acceptable, which fits with other research in the area. [23] While self-testing was valued, nearly all of those supporting home-testing would repeat the measurement in clinic, typically in order to perform an up-to-date reading. Practice and views became more positive with the implementation of remote monitoring due to the pandemic, though with much lower levels of acceptability than BP self-monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…There is a limited body of evidence on the accuracy and usefulness of self-testing for urine protein and urine glucose 27 30 . In a sample of pregnant women in the UK self-testing for urine protein gave 81% sensitivity and 93% specificity compared to laboratory reference standards 28 . There was no direct comparison made between self-measurement and measurements by healthcare professionals in this study, but similar estimates for sensitivity and specificity were found when healthcare professionals conducted the urine protein tests and these were compared with the laboratory reference standard potentially suggesting better agreement in this study compared to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Instructions in response to abnormal signs and symptoms were provided to patients for self-management interventions manually (n=6) [44,[47][48][49][50][51], automatically (n=4) [40,43,45,46], or both (n=4) [36,38,39,56], or they were unspecified (n=2) [42,57]. Manual instructions for patients and HCPs included written or verbal instructions, and automatically provided instructions were given through a digital platform, such as a mobile or web app or a web-based dashboard.…”
Section: Intervention Design and Implementationmentioning
confidence: 99%